Technological Study of mortars from historic monuments in Greece - Φωτοπούλου, Ιωάννα (Πανεπιστήμιο Πελοποννήσου, 2018)
In theoretical part, chapter 1, uses and types of historic mortars in Greece, especially building mortars, are reviewed. In chapter 2, also theoretical, the aims, results and limitation of analytical techniques used for the study of mortars are discussed. Presentation of experimental methodology and samples follows. Forty eight (48) samples were available for study. They were photographed, described macroscopically and initially grouped. XRF measurements were taken. Results proved difficult to evaluate without a more thorough study. A further selection of fourteen (14) samples was made, in order to be studied with other analytical and laboratory techniques. After the separation of aggregates and binder and the study of fractured surfaces and samples under a stereoscope, porosity measurements were made, XRD analysis of the fine powder produced (<0,063mm), SEM analysis (including EDX measurements of binder) and mechanical tests when adequate sample size was available. The discussion of the results has been divided in two parts: • comparative presentation for each technique (chapter 4.1 to 4.6) and • analytic presentation of results and observation on each sample (chapter 5.1 to 5.4). In conclusions, grouping of experimental results is made and evaluation of use of pXRF is attempted.
Keywords: Κονίαμα -- Ανάλυση; Κονίαμα -- Έλεγχος; Αρχαιολογική χημεία -- Μεθοδολογία; Αρχαιολογία -- Μεθοδολογία; Μνημεία -- Συντήρηση και αποκατάσταση -- Ελλάδα; Κονίαμα; Χημική σύσταση; Αρχαιολογική χημεία; Συντήρηση αρχαιοτήτων